Money, banking, and economy in Nigeria - Osiegbu, Patrick I. (Port Harcourt, Nigeria : Outreach Publications, 1999)
Highlights the historical antecedents of modern money, the advantages, functions, theories and characteristics. It also covers differenct facets of the Nogerian financial system, operations and policies.
Includes bibliographical references and index.
oif 26/02/2015, rua 10/04/2015
Loan
Keywords: Finance; Money; Banks and banking; Monetary policy; Financial services industry; Nigeria